Reality measure of the published GPS satellite ephemeris uncertainties. Issue 2 (4th May 2022) - Shirazian, Masoud; Jazireeyan, Iraj; Bagherbandi, Mohammad
ABSTRACT: The international GNSS service (IGS) started publishing the precise ephemeris files in the form of the standard products #3, version C (the sp3c files) in which the GPS satellite orbits and clocks and their uncertainties were available since 2004. Incorporating these uncertainties into the GPS observation equations results in a better stochastic model of the processing system. The reality of these uncertainties is questioned and studied in this paper. Precise point positioning (PPP) model, statistical tests and variance component estimation (VCE) techniques are employed for this study. The results confirm the efficiency of the proposed method in the assessment of reality of the published ephemeris uncertainties.